PENGARUH LATIHAN DOUBLE LEG HOP PROGRESION TERHADAP POWER OTOT TUNGKAI PADA TIM SEPAK TAKRAW SMA NEGERI 1 PUJUD KABUPATEN ROKAN HILIR - Iis Wadi; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrack: The problem in this research is that athletes are not maximal in jumps when blocking and hitting (nails). The title being investigated in this research is